BUILDING ONLINE COMMUNITY, COMMUNICATION STRATEGY, AND USES AND GRATIFICATION THROUGH THE STANDARD'S PODCAST PROGRAM - Parayard , Kanokwan; Banterng, Teerati (Journal of MCU Nakhondhat, 2023)
The objectives of this research were 1) To examine the creation of online communities from The STANDARD Podcast. 2) To investigate the communication strategies of the shows within THE STANDARD Podcast. 3)To study the uses and satisfaction of the audiences from THE STANDARD Podcast. This research follows a qualitative approach and involves interviewing a group of ten individual participants, including opinion leaders and general members of THE STANDARD Podcast's online community. The analysis is based on the content of two selected podcast shows from THE STANDARD, namely “KND Podcast” and “Readery”, which were among the top 10 most popular episodes throughout the year 2021. These episodes were chosen from the January to June 2021 period and comprised a total of 10 episodes, with 5 episodes from “KND Podcast” and 5 episodes from “Readery”. The selection criteria involved selecting episodes that received a substantial amount of comments. (1) The study findings indicate a decreased interest In online communities among individuals nowadays. In 2022, there has been a shift in the media consumption habits of individuals. Social media users are no longer inclined to use Facebook but are more interested in platforms such as TikTok or YouTube. (2) There has been a development in communication methods from audio podcasts to video podcasts. It has been observed that there are strategies in place to adapt and adjust the change in media trends to engage audiences. THE STANDARD Podcast, for example, has transformed its format from being solely an audio podcast to a video podcast. It is not only changing the format but also shifting the content’s show. (3) It has been discovered that the topics presented in the podcast are beneficial for personal development, allowing audiences to get valuable insights from the storytelling presented in particularly episodes and apply them to their daily lives.